Normative rugby data of the SARTS tests: Comparison of elite and school players - Olds, M.; Gadkari, P.; Adams, T. (International Journal of Sports Medicine, 2020)
This study aimed to examine the normative data for the SARTS rugby tests in elite and schoolboy rugby players. A second aim was to examine differences between level of sport and position of play in the SARTS rugby tests. Elite (N = 57) and Schoolboy (N = 63) rugby players performed the SARTS tests relevant to rugby players each for 1 min, with 1-2 min rest between each test. A 2×2 factorial ANOVA was used to assess for the main effect of player position and player level of play. Results showed that elite players performed more Ball Abduction External Rotation (BABER) (dominant and non-dominant), Side Hold Rotations (dominant and non-dominant), Ball Taps (dominant and non-dominant), and Overhead Snatch than schoolboy players. Heavier players performed fewer Push-up Claps. Injured rugby players should perform at least the mean value of the repetitions of the SARTS tests before returning to contact training after an injury.